Comparative Efficacy and Safety of Moxifloxacin and Levofloxacin in a Short Standardised Rifampicin Resistant TB Regimen: A STREAM 2 Secondary Analysis - Stella M. Fabiane; Chen-Yuan Chiang; Sarah K. Meredith; Meera Gurumurthy; Adamu Bayissa; Andrew J. Nunn; Ruth L. Goodall (Tropical Medicine and Infectious Disease, 2024)
(1) Background: The World Health Organisation (WHO) categorises moxifloxacin and levofloxacin as Group A drugs, which should be prioritised in the treatment of rifampicin-resistant tuberculosis. We compare their relative efficacy and safety using data from the STREAM trial; (2) Methods: Marginal structural models were used to balance differences in the baseline characteristics of participants receiving the STREAM control regimen containing either moxifloxacin or levofloxacin as this was not a randomised comparison. The difference in proportions between regimens was estimated for favourable outcome, any grade 3/4 adverse event, QTcF increase to ≥500 ms, QTcF increase from baseline by at least 60 ms, and any grade 3/4 adverse event excluding QT events, using weighted analyses; (3) Results: In efficacy analyses (n = 123), the weighted risk difference (moxifloxacin—levofloxacin, wRD) for a favourable outcome was −0.045 (−0.213, 0.123), p = 0.60. Similarly, estimates from the safety analyses (n = 127) showed no evidence of a difference between the fluoroquinolones, other than a suggestion of fewer QTcF increases from baseline on levofloxacin (wRD 0.160 (−0.026, 0.346), p = 0.091); (4) Conclusions: In this small dataset, we found no statistically significant difference in key efficacy or safety outcomes between the moxifloxacin- and levofloxacin-containing regimens; there was a suggestion that QTcF increases from baseline were fewer on levofloxacin.